2019
DOI: 10.3390/nu11071511
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequalities in the Retail Food Environment around Schools in a Southern European Context

Abstract: Across Europe, excess body weight rates are particularly high among children and adolescents living in Southern European contexts. In Spain, current food policies appeal to voluntary self-regulation of the food industry and parents’ responsibility. However, there is no research (within Spain) assessing the food environment surrounding schools. We examined the association between neighborhood-level socioeconomic status (NSES) and the spatial access to an unhealthy food environment around schools using both coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 70 publications
1
14
1
2
Order By: Relevance
“…At the interpersonal level, availability, accessibility, parental role modelling, parental permissiveness, family cohesion, parental concerns about child's health, parental norms, visibility of food items, methods of preparation, settings for eating, and parental monitoring were the most consistent correlates of dietary intake among youth . Exposure to unhealthy food outlets in the immediate food environment, food advertising, trade and agricultural policies, food prices and school food policies were also shown to be the factors influencing dietary intake.…”
Section: Introductionmentioning
confidence: 95%
“…At the interpersonal level, availability, accessibility, parental role modelling, parental permissiveness, family cohesion, parental concerns about child's health, parental norms, visibility of food items, methods of preparation, settings for eating, and parental monitoring were the most consistent correlates of dietary intake among youth . Exposure to unhealthy food outlets in the immediate food environment, food advertising, trade and agricultural policies, food prices and school food policies were also shown to be the factors influencing dietary intake.…”
Section: Introductionmentioning
confidence: 95%
“…This variability suggests the need to examine the accuracy of secondary data on a case-by-case basis [15]. To the best of our knowledge, our study is the first offering insight from a large Southern European setting, where there has been recent interest in food environment research [3,53].…”
Section: Discussionmentioning
confidence: 99%
“…Moving from the school setting to the surrounding neighborhood environment, Díez and colleagues [37] examined socioeconomic inequalities in the food environment around schools in Spain. They showed that 95% of the schools were surrounded by unhealthy food retailers within a short range, with a median of 17 unhealthy food outlets per school.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that 95% of the schools were surrounded by unhealthy food retailers within a short range, with a median of 17 unhealthy food outlets per school. A worrying addition to this was that unhealthy food retailers were both closer and higher in number for schools in low-SES neighborhoods [37], indicating that children from a lower SES background are growing up in a less healthy food environment. Dhillon and colleagues [38] painted an equally problematic picture regarding the food environment of college students living on a food-desert campus in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation